Surgical site infection after hip fracture surgery: a systematic review and meta-analysis of studies published in the UK. Issue 9 (1st September 2020) - Masters, James; Metcalfe, David; Ha, Joon Soo; Judge, Andrew; Costa, Matthew L.
Abstract : Aims: This study explores the reported rate of surgical site infection (SSI) after hip fracture surgery in published studies concerning patients treated in the UK. Methods: Studies were included if they reported on SSI after any type of surgical treatment for hip fracture. Each study required a minimum of 30 days follow-up and 100 patients. Meta-analysis was undertaken using a random effects model. Heterogeneity was expressed using the I 2 statistic. Risk of bias was assessed using a modified Newcastle-Ottawa Scale (NOS) system. Results: There were 20 studies reporting data from 88, 615 patients. Most were retrospective cohort studies from single centres. The pooled incidence was 2.1% (95% confidence interval (CI) 1.54% to 2.62%) across 'all types' of hip fracture surgery. When analyzed by operation type, the SSI incidences were: hemiarthroplasty 2.87% (95% CI 1.99% to 3.75%) and sliding hip screw 1.35% (95% CI 0.78% to 1.93%). There was considerable variation in definition of infection used, as well as considerable risk of bias, particularly as few studies actively screened participants for SSI. Conclusion: Synthesis of published estimates of infection yield a rate higher than that seen in national surveillance procedures. Biases noted in all studies would trend towards an underestimate, largely due to inadequate follow-up.